VALUASI EKONOMI YOUTH CAMP DI TAMAN HUTAN RAYA WAN ABDUL RACHMAN (Tahura WAR) - Rahmat Rizky Maulana; Bustanul Arifin; Zainal Abidin (Lampung University, 2021)
The study aims at analyzing travel costs, economic valuations, and factors affecting the frequency of tourist visits to Youth Camp in Wan Abdul Rachman Forest Park. The research was conducted at the Youth Camp in Wan Abdul Rachman Forest Park involving 73 tourist visitors selected by the method of taking moment. Data collection was conducted in November-December 2018. Travel expenses are analyzed by the analysis of travel expenses, economic valuation is calculated using the calculation of travel expenses and consumer surplus and factors that influence the frequency of visitor visits analyzed using regression Poisson. The study shows that the cost of travel borne by visitors to the Youth Camp in Wan Abdul Rachman Forest Park amounted to IDR77,188.13 per individual, the highest travel cost was from the cost of consumption and lowest was from the cost of documentation and miscellaneous charges. Factors affecting the frequency of tourist visits to Youth Camp in Wan Abdul Rachman Forest Park were cost of travel, income, distance, and facilities. Economic value of the Youth Camp in Wan Abdul Rachman Forest Park by using the method of travel costs was IDR1,924,199,.823,454.41.Key words: economic valuation, frequency of visits, travel costs, Youth Camp.